P-53 HELICOBACTER PYLORI INFECTION IN PATIENTS WITH PEPTIC ULCER DISEASE AND CIRRHOSIS OF THE LIVER - Jaime Fustamante; Eduardo Monge; Claudia Soto; Julio Narroquin; Lucero Torres (Annals of Hepatology, 2023)
Introduction and Objectives: An increased rate of peptic ulcer disease (PUD) has been described in patients with cirrhosis. Helicobacter pylori (Hp) infection rates are lower than in the non-cirrhotic population. Peru has a high prevalence of Hp infection, but there is no information on this association in our population. This study aimed to study the association between PUD and Hp in patients with cirrhosis. Materials and Methods: All patients with an endoscopic diagnosis of PUD between 2014 and 2019 at Daniel Carrion Hospital were reviewed. The frequency of Hp infection in patients with PUD with and without cirrhosis was assessed. Statistical differences were accepted with a p value < 0,05. Results: A total of 574 patients with PUD were included. 72(13%) had cirrhosis. In patients with cirrhosis, Hp was positive in 24 (33%); in those without cirrhosis, Hp was positive in 285 (57%), p <0,05. See table 1. In patients with cirrhosis and PUD and Hp positive, 83% were gastric ulcers. Of those without cirrhosis, 55% were gastric ulcers. Conclusions: There is a lower prevalence of Hp infection in patients with PUD and cirrhosis as compared with no cirrhotic PUD patients.